2021
DOI: 10.3389/fpsyg.2021.703531
|View full text |Cite
|
Sign up to set email alerts
|

Crossmodal Interactions Between Olfaction and Touch Affecting Well-Being and Perception of Cosmetic Creams

Abstract: In the present series of studies, we investigated crossmodal perception of odor and texture. In four studies, participants tried two textures of face creams, one high viscosity (HV) and one low viscosity (LV), each with one of three levels of added odor (standard level, half of standard, or base [no added odor]), and then reported their levels of well-being. They also reported their perceptions of the face creams, including liking (global liking of the product, liking of its texture) and “objective” evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In a similar vein, Churchill et al (2009) examined whether different pleasant scents added to shampoo would affect the perception of hair after washing, and found that the different odors affected the perception of hair texture characteristics, supporting the notion of a cross-modal interaction between scent and touch. Additionally, as mentioned earlier, scent can enhance the perception of texture in cosmetic lotions (Courrèges et al, 2021). Thus, tactile-olfactory interactions present a particularly fruitful area for future research in consumer behavior (Courrèges et al, 2021;Demattè et al, 2007aDemattè et al, , 2007bKrishna et al, 2010).…”
Section: Sensory Marketing and Cross-modal Effects On Product Perceptionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a similar vein, Churchill et al (2009) examined whether different pleasant scents added to shampoo would affect the perception of hair after washing, and found that the different odors affected the perception of hair texture characteristics, supporting the notion of a cross-modal interaction between scent and touch. Additionally, as mentioned earlier, scent can enhance the perception of texture in cosmetic lotions (Courrèges et al, 2021). Thus, tactile-olfactory interactions present a particularly fruitful area for future research in consumer behavior (Courrèges et al, 2021;Demattè et al, 2007aDemattè et al, , 2007bKrishna et al, 2010).…”
Section: Sensory Marketing and Cross-modal Effects On Product Perceptionmentioning
confidence: 94%
“…Additionally, as mentioned earlier, scent can enhance the perception of texture in cosmetic lotions (Courrèges et al, 2021). Thus, tactile-olfactory interactions present a particularly fruitful area for future research in consumer behavior (Courrèges et al, 2021;Demattè et al, 2007aDemattè et al, , 2007bKrishna et al, 2010).…”
Section: Sensory Marketing and Cross-modal Effects On Product Perceptionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, not all sensory modalities are involved equally in all stimuli, and specific cross-modal integration may be particularly relevant for specific context. For a cosmetic product, touch and olfaction are intuitively the two most important senses and their integration plays an important role in the perceptual decision guiding product utilisation behaviour [2]. In addition, state of the art in the actual cosmetic market shows that a given texture is usually more associated with particular families of fragrances and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…However, they use brush stroking as tactile stimulations which is far from the ones from cosmetic products [12]. To our knowledge, only one study by Courrèges et al [2] has focused on the influences of touch-smell cross-modal interaction on hedonic evaluation of a cosmetic product. They have shown that the addition of a fragrance increased well-being ratings and liking of a texture.…”
Section: Introductionmentioning
confidence: 99%